Current Perspectives on the Treatment of Obstructive Sleep Apnea - Part I - Peker, Yüksel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Obstructive sleep apnea is a highly prevalent disorder with strong associations with cardiovascular, cerebrovascular, metabolic, and cognitive consequences, including drowsy driving. Positive Airway Pressure treatment is the first-line therapy for adults with obstructive sleep apnea who are symptomatic. However, many individuals with comorbidities do not report symptoms that are associated with the disorder, and adherence to treatment is poor, especially in individuals with cardiovascular diseases. This reprint contains reviews and original articles that aim to update the current perspectives on the treatment modalities of obstructive sleep apnea to highlight multidisciplinary approaches, personalized treatment strategies, and the identification of the predictors of a patient's response to treatment, both in the general population and in clinical cohorts.